Dual-Focus Academic Coping Strategies of Students in Overcoming Presentation Anxiety at SMP Negeri 4 Waru - Abdulloh, Firman; Albaar, Ragwan (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study explores the dual-focused academic coping strategies of ninth-grade students at SMP Negeri 4 Waru in managing presentation anxiety. Using a descriptive qualitative method, three students were selected through purposive sampling. Data were collected via semi-structured interviews and classroom observations, then analyzed using thematic analysis. The findings show that students combine problem-focused coping (task preparation, repeated practice, and structured explanation) with emotion-focused coping (prayer, self-affirmation, and peer support). Teacher assistance strengthens students’ self-efficacy and reduces anxiety. These results contextualize Lazarus and Folkman’s coping theory within the Indonesian school setting and provide a foundation for guidance and counseling interventions to reduce academic performance anxiety.